1995
DOI: 10.2166/wst.1995.0399
|View full text |Cite
|
Sign up to set email alerts
|

Management of wastewater from the fertilizer industry

Abstract: Two schemes of treatment were applied to wastewater produced from a superphosphate manufacturing unit. In the first scheme the final effluent, comprising washing water from the scrubbing towers in combination with cooling water, was subjected to chemical coagulation-sedimentation using lime. In the second scheme the washing water from the scrubbing towers was chemically treated with recycling of a percentage of the treated effluent. The two treatment schemes were carried out using a continuous flow compact uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Treating this sludge in a sand drying bed with 36 cm filter depth and 50 cm total sludge depth at filling time, reduced its volume to 1.45 m 3 and increase its solid content to 16.6% after settling for 3 days. This is comparable to the published work by Abou-Elela et al, (1995) which indicates improvement of sludge filterability in sand bed with 20 cm depth and 32 cm maximum sludge depth. The results of this study show that 94% of water was lost from the sludge, mostly (87%) by leashing while 7% was evaporated.…”
Section: Approach Threesupporting
confidence: 91%
See 1 more Smart Citation
“…Treating this sludge in a sand drying bed with 36 cm filter depth and 50 cm total sludge depth at filling time, reduced its volume to 1.45 m 3 and increase its solid content to 16.6% after settling for 3 days. This is comparable to the published work by Abou-Elela et al, (1995) which indicates improvement of sludge filterability in sand bed with 20 cm depth and 32 cm maximum sludge depth. The results of this study show that 94% of water was lost from the sludge, mostly (87%) by leashing while 7% was evaporated.…”
Section: Approach Threesupporting
confidence: 91%
“…This is in agreement with Metcalf and Eddy who reported that most of the water losses in the sand drying bed is via under drain pipes, while little is due to evaporation. Also, Abou-Elela et al, (1995) reported little temperature effect on the performance of the sand bed of sludge drying. On the other hand, Al-Muzaini (2003) reported that drying municipal sewage sludge in the sand drying bed increase solid content up to 40% after 9 days in summer and 15 days in winter.…”
Section: Approach Threementioning
confidence: 99%
“…Chemical coagulation precipitation and biological treatment via aerobic systems were investigated. -Elela et al, 1995) was operated at the optimum pH and coagulant dose. A schematic diagram and specification of the treatment unit are given in Table 2 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An environmental bacterium, Citrobacter freundii , was engineered for overexpression of the polyphosphate kinase gene based on a solo medium-copy plasmid strategy that resulted in 12.7% poly-P accumulation by the cells, thus overcoming the negative regulation of PhoU (Wang et al, 2017). The negative regulation of PhoU is a major limitation to PO 4 3– -P bioremediation when the soluble PO 4 3– -P level is high in waste effluents, e.g., effluents from fertilizer industry (25–308 ppm of PO 4 3– -P) (Abou-Elela et al, 1995), parboiled rice mill industry (34–143 ppm of PO 4 3– -P) (Faria et al, 2006), and rice-based distilleries (223.5 ± 27.5 ppm of PO 4 3– -P) (Bhattacharyya et al, 2014). The screening and development of phoU mutants of PAOs was considered to be a solution to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%